2007
DOI: 10.1007/s10529-007-9553-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and properties of a light-insensitive rice catalase-B expressed in E. coli

Abstract: Catalase plays a central role in plant stress responses but is highly susceptible to photoinhibition. A rice catalase-B protein avoiding photoinhibition was developed by mutagenesis of specific amino acids: Leu-189 to Trp-189 and His-225 to Thr-225 and then recombinantly expressed in E. coli. In addition, the site specific mutation also induced 2-2.5-fold increase in enzyme velocity with high affinity for its substrate and showed nearly a 3-fold lower K(m) than the wild protein. These characteristic of mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Molecular identification and properties were performed in a light-insensitive Oryza sativa CAT B that was expressed in Escherichia coli (Mondal et al 2008b). The purification and expression of a soluble bioactive Oryza sativa CAT A from recombinant Escherichia coli have also been done (Ray et al 2012).…”
Section: Catalase Genomic Characterization Genes and Isoformsmentioning
confidence: 99%
“…Molecular identification and properties were performed in a light-insensitive Oryza sativa CAT B that was expressed in Escherichia coli (Mondal et al 2008b). The purification and expression of a soluble bioactive Oryza sativa CAT A from recombinant Escherichia coli have also been done (Ray et al 2012).…”
Section: Catalase Genomic Characterization Genes and Isoformsmentioning
confidence: 99%
“…2.1 Determination of the subunit size and comparison of the oligomeric status of WT and mutant IcSOD A mutant plasmid (Ser95Cys) was constructed following in vitro site-specific recombinant PCR and transformed into M15 cells for its overexpression. 20 The recombinant IcSOD proteins (WT and mutant) were purified to their homogeneity using Ni-NTA columns following protocols described earlier. 21 suggested that the sub-unit size of both the WT and mutant IcSOD was B17 kDa (ESI, † Fig.…”
Section: Resultsmentioning
confidence: 99%
“…and detoxifies the body, protect against mutagenesis and degenerative diseases [9]. Promising applications of catalases are in wastewater treatment, therapeutics, baking and brewing, pulp and paper industry [7,10]. Peroxidase has a potential for bioremediation of soil and wastewater contaminated with phenols, cresols, chlorinated phenols.…”
Section: Research Articlementioning
confidence: 99%